TANTANGAN TEKTONIKA DIGITAL - Robert Rianto Widjaja, M.T. (Universitas Katolik Soegijapranata, 2022)
The rapid development of digital technology has an impact on the ease of processing mass forms and the appearance of buildings in architecture. This significantly influenced tectonics as an important part of architecture. Tectonics is like finding a new window of view from the same existence. This situation demands an explanation of the position and role of tectonics in contemporary architectural works. This explanation is very important to rediscover the nature of tectonics as an art of construction in the new face of digital technology. This paper will examine the classical tectonic discourse that has developed from the core form and art form to the understanding of ontology and representation which is the beginning of the discussion of digital tectonics. Through a study of several relevant cases, it can be found that epistemologically, digital tectonic still has the same nature as classical tectonic. The difference lies in the richness of the quality and richness of the truth representation which implicitly gives birth to hidden truth conditions in digital tectonic representations. The existence of this hidden truth poses a challenge for digital tectonics to survive as the art of construction.